Hubungan Kualitas Pelayanan Rawat Inap dengan Minat Pemanfaatan Ulang Pelayanan di Puskesmas Kabupaten Pasuruan - Izza Afkarina Mutiara (Jurnal Informasi Kesehatan Indonesia (JIKI), 2022)
Background: Interest in service reuse will arise if the patient is satisfied with the services provided. Based on the research that has been done, the indicator value of hospitalization at Gempol Health Center is still low. The purpose of this study was to determine the relationship and strength of the correlation between the quality of inpatient services and the interest in service reuse at Gempol Health Center, Pasuruan Regency. Subjects and Method: This research is a quantitative research with a cross sectional design. The sampling method used was accidental sampling with a sample size of 30 people and used the contingency coefficient test. Results: The results showed that there was a significant relationship between the quality of inpatient servicesn and the reuse of services at the Gempol Health Center, Pasuruan Regency with p = 0.000 and r = 0.658. Conclusion: There is a significant relationship between the quality of inpatient services and the interest in reusing the services of BPJS participants at Puskesmas Gempol, with the strength of the correlation between the two variables being strong. Keywords: quality of inpatient services, interest inservive reuse